Exposure to Bullying Behaviors at Work and Depressive Tendencies: The Moderating Role of Victimization From Bullying During Adolescence - Hoprekstad, Øystein Løvik (Journal of interpersonal violence, 2021)
The detrimental effects of exposure to bullying behaviors at work on employees’ mental health have been thoroughly documented. However, few studies have examined whether employees’ prior experiences with bullying may affect the strength of this relationship. The present study tested a model where victimization from bullying in adolescence was expected to (a) predict higher exposure to bullying behaviors at work and higher levels of depressive tendencies in adulthood and (b) strengthen the relationship between exposure to bullying behaviors at work and depressive tendencies (i.e., make employees more vulnerable). The hypotheses were tested using prospective data following a cohort of 536 Norwegian respondents over a time span of 17 years, from adolescence (age of 13) to adulthood (age of 30). Victimization from bullying in junior high school was measured at the age of 13, 14, and 15, and retrospectively at the age of 18. Exposure to bullying behaviors at work was measured at the age of 30, while depressive tendencies were measured at the age of 15 and at the age of 30. As predicted, those who had been bullied more (vs. less) in adolescence tended to have higher scores on depressive tendencies as adults and reported somewhat higher exposure to bullying behaviors at work. However, contrary to our predictions, the relationship between exposure to bullying behaviors at work and depressive tendencies in adulthood was weaker among those who had been bullied more (vs. less) in adolescence. The findings contribute to the scarce literature on the role of employees’ prior victimization experiences and question the notion that prior victimization from bullying produces long-term vulnerability to future experiences of bullying.